(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
The diagnosis of typhoid fever currently depends on isolation of Salmonella Typhi from blood. The sensitivity of blood culture is very low due to prior antibiotic treatment which is a common practice in Bangladesh. The sensitivity of blood culture also decreases at later stage of the disease. Widal test is the most utilized test in Bangladesh next to blood culture because it is inexpensive, less invasive. But the result of the test is controversial due to false negative & false positive results in some cases. In this study, a recently introduced polymerase chain reaction-based technique (which has 100% specificity for S. Typhi) was compared with widal test among 80 clinically suspected typhoid fever cases. Among 80 cases, the respective figures of positivity for PCR & widal test were 70% & 43.75% respectively. It can be concluded that PCR based technique is more sensitive & much superior to widal for diagnosis of typhoid fever. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22683 Bangladesh J Physiol Pharmacol 2014; 30(2): 46-50